PENGEMBANGAN E-COMMERCE SISTEM PEMASARAN BUKU ROHANI PADA TB.ABDI KARYA DENGAN METODE USER CENTERED DESIGN - Jenni Veronika Ginting; Zekson Arizona Matondang (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2019)
User Centered Design is a design philosophy that places users as the center of a system development process. The difficulty of users so far in reading and translating documents in each development can be helped by using the UCD method. User Centered Design can be applied in the development of a system, in this study applied in a system of spiritual book insertion in the book store Abdi Karya. The UCD approach has been supported by various techniques, methods, tools, procedures and processes that help design interactive systems that are more user-centered. In the UCD method the user is in the level of design sophistication of all the graphical interfaces used and the content of the admin information. When interacting with admin information users must get the same comfort in accordance with their experience using other systems.